Voltammetric determination of dinitronaphthalenes using a silver solid amalgam paste electrode - Tvrdikova, Jana; Danhel, Ales; Vyskocil, Vlastimil; Barek, Jiri (Analytical sciences, 2012)
The electrochemical behavior and application of a new sensor, a silver solid amalgam paste electrode (AgSA-PE), based on the mixture of a fine silver solid amalgam powder (60:40 (w(Hg)/w(Ag))) and a suitable organic pasting liquid (Paraffin oil) in a ratio of 20:1 (w/w), was investigated in an aqueous-methanolic media (1:1). This alternative working electrode provides simple preparation and handling, adequate mechanical stability, easily renewable electrode surface, sufficiently wide cathodic potential window (up to -1200 mV within a pH range of 2.7-12.3), and sufficient sensitivity without any necessary pretreatment. The practical usability of the AgSA-PE was verified by the development of voltammetric methods for the determination of selected environmentally important pollutants (1,3-, 1,5-, and 1,8-dinitronaphthalenes) in an aqueous-methanolic media (1:1). The differential pulse voltammetric methods at AgSA-PE give linear concentration dependences in the range of 1-100 µmol l(-1) with limits of detection of about 1 µmol l(-1) in a mixture of Britton-Robinson buffer of appropriate pH and methanol (1:1).